A study of the fresh and mechanical properties of concrete with open-heap burned rice husk ash (RHA) as a partial cement substitute and as a pozzolanic material - Jorillo, Pablo A.
This is an experimental study on the fresh and mechanical properties of concrete with rice husk as a partial cement substitute and as a pozzolanic material. The ash used in the experiments is the open-heaped up burnt and unground rice husk ash, which is very much available in the countryside. Ashes at different degrees of fineness were introduced to four kinds of grades of concrete. To determine the mechanical properties of concretes with different percentages of ash the following tests were applied: axial compression at three curing ages, split tension, third point flexure, and modulus of elasticity tests. for the fresh properties the time of setting concrete mixture, air content and plastic density were measured.